Impact of graduated compression stockings on the prevention of post-thrombotic syndrome - results of a randomized controlled trial. (September 2015) - Jayaraj, Arjun; Meissner, Mark
Objective: Post-thrombotic syndrome is a chronic complication of acute deep venous thrombosis in the lower extremity. The role of graduated compression stockings in the prevention of post-thrombotic syndrome has been studied with opinion being divided on the beneficial effects. We aim to answer this question with a randomized controlled study that uses multiple scoring instruments to assess post-thrombotic syndrome. Methods: Sixty-nine consecutive patients with acute deep venous thrombosis diagnosed by duplex ultrasonography were randomized to treatment with graduated compression stockings or no graduated compression stockings. Venous Clinical Severity Score and Villalta-Prandoni Score, commonly used scoring systems, were used to appraise post-thrombotic syndrome at 3, 6, 12, 18, and 24 months following diagnosis of deep venous thrombosis. In both scoring systems, the individual either had post-thrombotic syndrome or no post-thrombotic syndrome. Cumulative incidence was computed using Kaplan–Meier analysis. Relative risk was assessed for age, obesity, varicose veins, and iliofemoral deep venous thrombosis. Results: As measured by both Villalta-Prandoni Score and Venous Clinical Severity Score instruments, the graduated compression stockings group had a lower incidence of post-thrombotic syndrome compared to the control group, but only when one month was used as cut off time for the first diagnosis of post-thrombotic syndrome. When 6 or 12 months were used, there was no difference in the incidence of post-thrombotic syndrome between the two groups. The burden of post-thrombotic syndrome was significantly more when the Villalta-Prandoni Score instrument (∼75%) was used as compared to the Venous Clinical Severity Score instrument (∼30%) at 24 months' follow-up. Obesity was the only statistically significant predictor for the development of post-thrombotic syndrome. Conclusion: As assessed by both Villalta-Prandoni Score and Venous Clinical Severity Score instruments, use of graduated compression stockings does not reduce the incidence of post-thrombotic syndrome. There is a significant difference in the incidence post-thrombotic syndrome as detected by Villalta-Prandoni Score and Venous Clinical Severity Score instruments with incidence of post-thrombotic syndrome dependent on instrument and cut off time interval used to assess post-thrombotic syndrome. However, larger prospective studies are required to confirm these differences.